2006
DOI: 10.1038/sj.ki.5000057
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of de novo ceramide synthesis in radiocontrast-induced renal tubular cell injury

Abstract: We reported previously that various radiocontrast media cause apoptosis in porcine proximal tubular (LLC-PK(1)) cells, in which reduction in B-cell lymphoma (Bcl)-2 expression and caspase-3 activation are implicated. In the present study, we investigated a role for ceramide in radiocontrast media-induced apoptosis in renal tubular cells. LLC-PK(1) cells were exposed to radiocontrast media for 30 min, followed by incubation for 24 h in normal medium. Cell viability was assessed by 2-(2-methoxy-4-nitrophenyl)-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 44 publications
(58 reference statements)
2
52
0
1
Order By: Relevance
“…Previous cellular studies have determined that high ceramide levels cause renal damage, for example (Itoh et al ., 2006), but few have examined specific carbon chain lengths. One study reported higher absolute values of ceramides C16:0, C22:0, and C24:0 in the kidney extracted from CD‐1 mice 2 and 18 h after ischemia–reperfusion injury (Kalhorn & Zager, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Previous cellular studies have determined that high ceramide levels cause renal damage, for example (Itoh et al ., 2006), but few have examined specific carbon chain lengths. One study reported higher absolute values of ceramides C16:0, C22:0, and C24:0 in the kidney extracted from CD‐1 mice 2 and 18 h after ischemia–reperfusion injury (Kalhorn & Zager, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…34 Another study by Heinrich et al 35 showed no difference in toxicity on LLC-PK 1 cells between iodixanol and iomeprol over a broad range of concentrations and incubation times. In a study by Itoh et al 36 it was shown that iotrolan reduced the cell viability (determined by WST-8 assay), whereas iodixanol did not. The two contrast media have about the same osmolality, and hence other properties than osmolality must have been responsible for the decrease in cell viability induced by iotrolan.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to renal medullary hypoxia and parenchymal injury due to accelerated production of free radicals by renal tubular epithelial cells 10. As contrast medium flows through the renal tubules, it gradually becomes highly concentrated, and toxicity of the agent itself can directly damage tubular epithelial cells 11, 12, 13. Emergency investigations and treatment often require use of a contrast medium, even in patients with a high risk of CIAKI.…”
Section: Areas Where Clinical Application Of Hydrogen Gas Is Expectedmentioning
confidence: 99%